Sunteți pe pagina 1din 14

Beta and Gamma Functions

If (i) the interval [a, b] is finite


(ii) the function f(x) is bounded in [a, b], that is, f(x) does not become infinite at any point in the
interval, and
b

d
[ ( x ) ] =f ( x ) , then
dx

(iii)

f ( x) dx
a

= (b) - (a) is called a proper integral.


b

In condition (i) is not satisfied (that is, a, b or both are infinite), the integral

f ( x)dx
a

is

called an improper integral of first kind.


1

Definition: If m and n are positive, then

x m1 (1x )n1 dx
0

is called a Beta function and

denoted by B(m, n) or (m, n).


Note: If m and n are both greater than or equal to 1, then the above integral is a proper integral.
On the other hand if either m or n is less than 1, then the integral becomes improper but may be
convergent.
Properties of Beta Functions:
1. Symmetry: B(m, n) = B(n, m)
1

x m1 (1x )n1 dx

Verification: By definition, B(m, n) =


(1(1x ))

m1
(1x)

=
1

f ( ax ) dx
a

(since

(1x)m1 x n1 dx
0

f ( x ) dx=
0

x n1 (1x )m1 dx

= B(n, m).

cos d

p
2. If p > -1, q > -1 then sin

1
2 B

( p+2 1 , q +12 ) .

sin

cos d

sin p

Verification:

( 2 )

( p1)
2

cos
( 2 )

(q1)
2

sin cos d

Put sin2 = x. Then cos2 d = 1- x.


When = 0, we have x = 0 and =

Therefore

sin

cos d

(
1
x

2 0

1
2 B

p+1
1
2

2 , we have x = 1.

x
=
0

p1
2

(1x)

q 1
2

1
. dx
2

q +1
(
)1
( 1x ) 2 dx

( p+2 1 , q +12 ) .

Note: By taking

p+1
2

= m and

2 m1

Therefore B(m, n) = 2 sin


0

q+1
2

= n, we get p = 2m-1 and q = 2n-1.

cos 2n1 d .

3. B(m, n + 1) + B(m + 1, n) = B(m, n).


B(m, n+1)
n

4.

B(m+1, n) B(m, n)
=
m
m+n

Verification: Left to the students practice

Definition: If n is positive then

ex x n1 dx
0

is called a Gamma function denoted by (n).

Properties of Gamma function:


Property 1: (1) = 1

Verification: By definition (n) =

ex x n1 dx .
0

ex x 0 dx

Therefore (1) =

ex dx
=
0

lim ex e 0
x

[ ]
e
1

= -(0-1) = 1.

Property 2: Reduction formula: (n + 1) = n (n).

Verification: By definition, (n + 1) =

[ ( )]
x

e
x
1
n

ex n1

- 0 1 n x dx

= -(0-0) + n(n) = n (n).

ex x n dx
0

. Applying integration by parts, (n + 1) =

xn

lim
0 + n ex x n1 dx
x
=
x e
0

Property 3: If n is a positive integer then (n) = (n-1)

Verification: (n + 1) = n (n). Changing n to n-1, we get (n) = (n-1)(n-1). Similarly


(n -1) = (n -2)(n-2).
By substitution (n) = (n-1) (n-2)(n-2).
Similarly, (n - 2) = (n -3)(n-3), and again by substitution, (n) = (n-1)(n-2)(n-3)(n-3).
This process can be continued successively, and it ends with (1), since n is a positive
integer.
Therefore (n) = (n-1) (n-2)(n-3) 1(1). But (1) = 1.
Hence (n) = (n-1) (n-2)(n-3) 1.
Property 4: Relation between beta and gamma function:

B ( m , n )=

(m) (n)
(m+ n) .

et t n1 dt

Verification: By definition,

, using t as the variable.

Put t = x2. Then dt = 2x dx.


When t = 0, we have x = 0 and when t = , we have x = .
x 2

x
( 2)n1 2 xdx

Therefore (n) =

ex x 2 n1 dx .
= 2
0

ey y 2 n1 dy .
Similarly (m) = 2
0

e
Multiplying, (m) (n) = 2
0

2 n1

dx

ey y 2 n1 dy
2
0

e(x + y ) x 2n 1 y 2 n1 dxdy
= 4
0 0

The range of this integral is the entire first quadrant of the XOY plane. Converting to polar
coordinates, by writing x = r cos , y = r sin so that dx dy = r d dr.

The limits being from 0 to

and r from to .

r
2 n1
r d dr
Therefore (m) (n) = 4 e (r cos )

0 r =0

= 4

sin

2 m1

cos

2 n1

0 r =0

er ( r)2 (m+n)1 dr

r=0

( 12 B (m ,n))( 12 (m+n))

=4

= B(m, n) (m + n).

Property 5:

( 12 )=

Verification: Use

( 12 )=2

B ( m , n )=

( m) (n)
1
m=n=
,
by
taking
2 , we get
(m+ n)

1
1
( ) ( )
1 1
2
2 . But (1) = 1.
B , =
2 2
(1)

( )

2( )1
2( )1
1 1
2
2
cos
d
Therefore B , =2 sin
2 2
0

( )


sin

cos

2
0

=2

( 2 0)= .

1
Therefore ( 2 ) =

Now (n) = (n-1)(n-1) (n-1) =

Put

n=

1
2 , we get

1
(n ).
n1

( 12 )= 11 ( 12 )
2

Property 6: Duplication formula: (m)

= -2

( 12 )

m+

(2 m)
2 m 1

(m) (n)
Verification: B ( m , n )= (m+ n) .
(m) (m)
Therefore B ( m , m )= (m+m)

[ (m)]2
(2m)

But

B ( m , m )=2 sin2 m1 cos 2 m1 d =


0

______(equation 1)

2
2

2 m 1

( 2 sincos )2 m 1 d
0

2
2 m 1

( sin 2 )2 m1 d

1
d . When = 0, we have = 0 and when =
2

Then d =

1
2 m 1

2 ( sin )

2 m1

we get = .

( sin )2 m1 12 d
0

2 sin 2 m1 cos
2 m 1

( 12 )1 d

1
=

2 m1

Therefore B(m, m) =

. Put 2 = .

2 m 1

1
B( m, )
2 =

1
2

2 m 1

(m).

( 12 )

1
(m+ )
2

_______(equation 2).

Hence from (1) and (2) we get

( m) .

( 12 ) .

[ (m)]
1
= 2 m1
1
(2m) 2
(m+ )
2

(m)

( 12 )

m+

(2 m).
2 m 1

Cancelling (m) both sides and write ( 2 ) =

we get

n1

(log 1y )

Property 7: (n) =

dy

ex x n1 dx

Hint: Use (n) =

. Put e-x = y so that ex = y or x = log

1
y .

Example: Evaluate

x 4 (1x)3 dx
0

Solution: By definition

x m1 (1x )n1 dx
0

= B(m, n).

Take m = p + 1 and n = q + 1.
1

We get

x p (1x )q dx
0

= B(p+1, q+1).

Therefore

x 4 (1x)3 dx
0

(5) (4)
(5+ 4)

= B(5, 4) =

4!3!
8!

1
.
280

Example: Evaluate

sin5 cos7 d
0

Solution: Use

sin p

cos d

sin5 cos7 d

1
2 B

( 62 , 82 )=

Example: Evaluate

( xa ) p (bx)q dx
0

Solution: Put x = a + (b - a)t.

1
2 B

( p+2 1 , q +12 ) .

1 (3) ( 4)
2 (7)

1
= 2

2!3!
6!

1
.
120

Then dx = (b - a)dt, x a = (b - a)t, b x = (b - a)(1- t).


When x = a, we have t = 0 and when x = b we have t = 1.
1

Therefore

( xa ) p (bx)q dx
0

p
q
[(ba)t ] [ (ba)(1t) ]
0

(ba)

p +q+1

t p [(1t)]
0

(b-a)

p+ q+1
( ba )
B p+1, q+1).

d
d
sin

sin d

Example: Show that

cos q d

Solution: Use sin

sin

1
2

2 B

cos d

sin d = 2 B
0

sin
0

1
2 B

1
+1
2
0+1
,
2
2

( 34 , 12 )

Taking p = -1/2, q = 0, we get

= .

( p+2 1 , q +12 ) ,

taking p = and q = 0, we get

_______(equation 1)

1
2

cos d

2 B

1
+1
2
0+1
,
2
2

d
d
sin

1
2 B

( 14 , 12 )

________(equation 2).

Multiplying (1) and (2)

d
d
sin

sin d
0

1
2 B

( 34 , 12 ) 12 B ( 14 , 12 )

[ ( )] ( )

1
1

.
2
4
1

4
5

()

1
4

2
[ ] . 1

(4)

5
( )
4

( 14 )

1
4 1
1
( )
4
4

= .

Example: Show that

ex dx
0

Solution: By definition of gamma function (n) =

et t n1 dt
0

. Put t = x2.

Then dt = 2x dx. When t = 0, we get x = 0; when t = we get x = .

Therefore (n) =

ex ( x 2)
0

Taking n = 1/2, we get

n1

2 xdx =

ex x2 n1 dx
0

1
( 2 ) = 2

(12 )1

dx

ex dx

Therefore

.
2

Example: Evaluate

x 4 a2x 2
0

Solution: Put x2 = a2t. Then dx =

dx

1
2 t

dt

When x = 0, we have t = 0; when x = a, we have t = 1.


a

x 4 a2x 2

Therefore

a 4 r 2 a 2a2 t 2a t dt

a6
t 2 ( 1t ) 2 dt

2 0

a6 3
1
B + 1, +1
2
2
2

a
5 3
B ,
2
2 2

a6

( )

5 3

2 2

( ( ))
(4 )

dx

e x dx = 2 ex dx .
= 2
0
0
x

31
1

a 22
2
2
3!

a
32

Example: Show that tan d

Solution:

tan d=
0

sin

1
2

sin
cos

1
2

cos d

1
1
+1
+1
1
2
2
B
,
2
2
2

1
3 1
B ,
2
4 4

( )

)
( 14 ) ( 34 )
1 3
( + )
4 4

Using Duplication formula with m =

( 14 ) ( 34 )
(1)

1
4

( 14 ) ( 34 )= ( 14 ) ( 14 + 12 )= 2 ( 12 )
1
1
2

Therefore

tan d=
0

1
2
2

, we get

2 .

2 .

Example: Express

dx

(1x 4 )

in terms of gamma function.

1
Solution: Put x = sin . Then dx= 2 sin
2

Therefore

dx
(1x 4 )

1
2

cos d .

1
2

12 sin cos2 d
0
(1sin )
=

1
2

sin

1
2

1
+1
2

2
1
2 2
1
+2
2

( )
( )

( 14 )
3
( )
4

Exercises:
1
3
1. Compute (3.5), (4.5), ( 4 ) ( 4 )

2. Express

x n ea x
0

in terms of gamma function.

xa

ba m +n+1 B ( m+1, n+1 ) .


3. Prove that

1x 3 10 dx
x5
1

4. Evaluate

x 2 dx
dx

=
4
4
5. Prove that
4 2 .
0 (1x )
0 (1+ x )